SOCIO-ECONOMIC AND POLITICAL SITUATION IN DAGESTAN IN THE PERIOD OF THE FIRST WORLD WAR - Idrisov, U M; Abdusalamov, M -PB (History, Archeology and Ethnography of the Caucasus, 2015)
The article examines the socio-economic and political situation in Dagestan during the First World War. The war led to the decline of not only agriculture, decline in industrial output, lower incomes, but also a sharp aggravation of the political situation in Dagestan.
Keywords: War; Dagestan; "Wild Division"; the Muslim clergy; shortage; mobilization; revolutionary processes